Immunitet egzekucyjny państw obcych: [Executive immunity of foreign countries] (Studia Prawnicze / The Legal Studies, 1967)
The problem of executive immunity of a foreign country relates recently to current interest due to vivid activity of countries in civil cases and international relationships.The paper deals only With the immunity of a foreign country in a court execution. There (still tils the administrative execution, and not pertaining to the discussed subject the arbitration execution, and execution by Virtue of titles coming from arbitration commissions that function at entreprises. And a foreign country cannot be a subject of the arbitration procedure of a procedure before the arbitration commission by an entreprise.Solutions regarding the executive immunity of a foreign country are of importance for (immunity in security procedure since they decide upon a question of immunity in this procedure.With regard to the problem (whether there exists lan identity between juridical immunity in civil process and executive immunity, two standpoints are to be found in science of law. Some authors are of opinion that subjection to the jurisdiction by a foreign country does not mean a waiver of an executive immunity. On the other hand, from the point of view of others there exists identity of immunities, hence, according to their opinion, waiver of juridical immunity means waiver of executive immunity.In the author’s opinion, the idea of identity of immunities cannot be accepted since between civil process and execution there exists a distinct boundary, the structure of both procedures is different, and execution processing has many independent elements.Execution immunity of a foreign country does not mean that a country as an obligee cannot claim for its dues by way of an execution. On the contrary, as an obligee it has full rights to do so provided that execution title is obtained.Analysis of the execution immunity requires a statement that:a. it concernas only the execution of titles proper for execution (sentences);b. investigation includes only accomplishment of execution title against a foreign country by domestic execution bodies;c. the scope oif study does not include recognition and accomplishment of pronouncement of foreign courts of justice.The comparison of legislations indicates that there are several categories of regulations: 1) absolute execution immunity of a foreign country (English-American system); 2) limitation of immunity depends upon a consent of Minister of Justice in each case (Italy, Greece); 3) execution Immunity exists with no regard to the process immunity ,(Belgium); 4) execution immunity is a subject of renunciation (France, Germany); 5) absence of immunity in the cases sure gestionis (Switzerland), and finally - in the USSR the execution on property of a foreign country depends upon a consent of competent organs of a country concerned.If it may be said that ,in modern countries there are developed tendencies to eliminate process immunity of foreign countries, it is, however, not to be observed as regards execution. Even more, there is to be seen a distinctive separation of both immunities.Analysis of diplomatic immunity points to that renunciation of immunity in a process does not mean renunciation of immunity in the execution which is to be stated explicitly. Even in the case of renunciation of immunityin the execution certain execution works cannot be done.In the socialist science of law immunity of a foreign country is a principle; to the exceptions the narrowing interpretation may be applied . From a voluntary .application with the case of a foreign country for consideration of the domestic court of justice cannot be drawn the conclusion that there is renunciation of the execution immunity.In Polish Code of Civil Procedure there exists immunity for Treasury of Polish State against which no execution is to be proceeded.Polish Code of Civil Procedure does not say directly about immunity of foreign countries, in Polish scence of law, however, its existence is not negated. To this leads the analysis of regulations in Art. 1111 and 1112 of Polish Code of Civil Procedure that allow exemption from domestic jurisdiction. Genesis of the mentioned regulations points to the legislator’s intention to protect by immunity also a foreign country. Adjudication proves that there have been cases in which a foreign country has been granted the immunity. The regulations of Polish Code of Civil Procedure of 1964 brought the formulation comprised in Art. 1115, § 2 that permits to draw the conclusion that renunciation of immunity in execution may occur only in a distinct way, and that a foreign country takes advantage of the immunity on the first place. It is to be considered whether immunity extends on immobilities, state entreprises, and bequensts with no heir.Consequently to the regulations of the Code of Civil Procedure the old conception is not to be accepted in this that a foreign country by purchasing a real estate is completely subjected to the Polish process law.Explicit renunciation of immunity made by a foreign country is a condition of allowability to the execution to be performed on a real estate bellonging to a foreign country.According to the Polish law state entreprises are selfexisting legal persons. The Code provides that execution may be effected from a hank account of a state entreprise. Execution from another property is inadmissible. Durable resources assigned to a state entreprise constitute the property of the state. The regulations to be applied in execution with regard to Polish state entreprises are also binding, for other entreprises in Poland unless they are not legal persons but constitute a part of the State Treasury. As regards beguests with no heirs the analysis of regulations proves that they are not subject of execution immunity.Execution against a foreign country is admissible under the explicit renunciation of immunity made by a foreign country. The execution may be proceeded in such a case as to be against a legal person. Application of the regulations on Treasury of Polish State in the case in which a foreign country is involved would prevent from proceeding the execution.